Noble metal nanoparticle-cerium monatomic catalyst, preparation and application

CN118847102BActive Publication Date: 2026-10-20BEIJING SINGLE ATOM SITE CATALYSIS TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410914729.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-09
Publication Date
2026-10-20
Estimated Expiration
2044-07-09

AI Technical Summary

Technical Problem

然而,尽管已有研究表明小尺寸的CeO2拥有更强的氧化-还原活性,目前将CeO2分散至单原子尺度并与其他活性金属复合组装成的催化材料报道较少

Benefits of technology

[0023]本发明的催化剂具有如下效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118847102B_ABST
    Figure CN118847102B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of noble metal nanoparticles-cerium monatomic catalyst, preparation and application, the catalyst includes metal oxide carrier and the noble metal nanoparticles and cerium monatomic supported on it, the oxide carrier is selected from any one, two or the mixture of multiple of γ-Al2O3, SiO2, TiO2;The noble metal is selected from any one or more of rhodium, ruthenium, platinum;Wherein, the noble metal is supported on carrier in the form of nanoparticle, and the cerium is supported on carrier in the form of monatomic site;The present application further discloses the solid-phase catalytic use of the noble metal nanoparticles-cerium monatomic catalyst, including methane carbon dioxide reforming to prepare synthesis gas or carbon monoxide oxidation to generate carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a catalyst material with adjustable loading of noble metal nanoparticles (0-2% by mass) and cerium single atoms (1-10% by mass) and its preparation method. This catalyst can be used for the catalytic reforming of methane and carbon dioxide to syngas, belonging to the fields of natural gas chemical engineering or environmental pollutant purification technology. Background Technology

[0002] CeO2 is renowned for its unique properties, low price, and excellent performance, attracting significant attention in both academic research and practical applications. Metal-CeO2 catalytic materials are primarily used in the environmental and energy sectors, playing an increasingly important role in petroleum cracking, industrial flue gas denitrification, vehicle exhaust purification, and volatile organic compound (VOCs) treatment. This is due to the unique electronic configuration of Ce ([Xe]4f...). 1 5d 1 6s 2 CeO2 contains Ce 4+ It can be easily transformed into a stable Ce 3+ CeO2 undergoes reversible switching within a redox cycle. To maintain charge balance, reactive oxygen species are generated and released on the CeO2 surface, while the generated oxygen vacancies can be filled by oxygen-containing molecules (such as O2, H2O, and CO2). This reversible transition, known as an "oxygen buffer," enables CeO2 to act as a reactive oxygen support, thus allowing noble metal nanoparticle-CeO2 catalysts to play a crucial role in many heterogeneous catalytic processes, such as three-way catalysis in automotive exhaust treatment. However, despite existing studies demonstrating that smaller CeO2 exhibits stronger redox activity, there are currently few reports on catalytic materials composed of CeO2 dispersed at the single-atom scale and assembled with other active metals. Limited by suitable preparation methods, the synergistic catalytic effect of Ce single atoms dispersed on oxide supports and active metals remains to be explored.

[0003] In view of the above, it is indeed necessary to provide a noble metal nanoparticle-cerium single-atom catalyst material and its preparation method that is applicable to various oxide supports, various active metals and has adjustable loading. Summary of the Invention

[0004] This invention discloses a noble metal nanoparticle-cerium single-atom catalyst material, which includes an oxide support and noble metal nanoparticles and cerium single atoms loaded on it.

[0005] The core components of the catalyst are as follows: the oxide support is selected from any one, two or more of γ-Al2O3, SiO2, and TiO2; the noble metal includes any one or more of rhodium, ruthenium, and platinum, and is loaded on the support in the form of nanoparticles; the cerium is loaded on the support in a single-atom site state; the loading of noble metal based on the total weight of the catalyst is 0.01-5% by mass, preferably 0.01-2%, and the loading of cerium is 0.01-15% by mass, preferably 1-10%.

[0006] The carrier is preferably γ-Al2O3, SiO2 or TiO2.

[0007] The catalyst is preferably Rh-Ce1 / Al2O3, Rh-Ce1 / SiO2, Rh-Ce1 / TiO2, Ru-Ce1 / Al2O3, or Pt-Ce1 / Al2O3, wherein the noble metals rhodium, ruthenium, and platinum are anchored on the oxide support in the form of nanoparticles, and cerium is uniformly dispersed on the oxide support in the form of single atomic sites; the loading of noble metals based on the total weight of the catalyst is 0.01-5% by mass, preferably 0.01-2%, and the loading of cerium is 0.01-15% by mass, preferably 1-10%.

[0008] This invention discloses a noble metal nanoparticle-cerium single-atom catalyst material and its preparation method, comprising the following steps:

[0009] S1: Pre-reduction of the oxide support;

[0010] S2: A solution is formed by mixing a soluble metal salt with a solvent, and then an oxide carrier is added and stirred until homogeneous;

[0011] S3: The mixture obtained from S2 is desolventized and calcined at high temperature to obtain a solid powder;

[0012] S4: High-temperature reduction of hydrogen gas yields catalyst powder;

[0013] In step S1, the reduction is carried out in a reducing atmosphere at a temperature of 300-500°C. The reducing atmosphere is hydrogen or a mixture of hydrogen and an inert gas, such as a hydrogen / argon mixture, wherein the hydrogen concentration in the mixture is 5-10% by volume, and the reduction time is preferably 1-4 hours.

[0014] The oxide support is selected from any one, two or more of γ-Al2O3, SiO2, and TiO2.

[0015] In step S2, the soluble metal salt is composed of a soluble noble metal salt or a noble metal complex and a soluble cerium salt. The soluble noble metal salt is selected from inorganic salts, inorganic acids, and organic acid salts of noble metals such as rhodium, ruthenium, and platinum; the soluble cerium salt is selected from inorganic salts or organic acid salts of cerium. The soluble ruthenium salt is preferably ruthenium nitrite or ammonium chlororuthenate; the soluble rhodium salt is preferably rhodium nitrate or rhodium chlorochloride; the soluble platinum salt is preferably tetraammineplatinum nitrate or chloroplatinic acid; the soluble cerium salt is selected from any one or a mixture of two of cerium nitrate, ammonium cerium nitrate, and cerium chloride. The solvent is deionized water or C64. 1-4 Alcohols, preferably ethanol.

[0016] In the metal precursor solution formed in step S2, the total concentration of metal salts is 0.018-0.02 mol / L. Different amounts of noble metals and cerium salts are added depending on the designed loading of noble metals and cerium.

[0017] In step S3, the solvent removal method is selected from heating evaporation, vacuum evaporation, vacuum heating evaporation, or freeze drying. For example, the precursor solution is heated to the solvent evaporation temperature, which is 40-100°C, to remove the solvent and obtain a solid powder. The high-temperature calcination temperature is 400-800°C, the calcination atmosphere is air, and the calcination time is preferably 4-8 hours. The obtained powder is then calcined in air at high temperature to remove chloride ions, nitrate ions, ammonium ions, etc.

[0018] In step S4, the reduction temperature is 600-800℃, the reduction atmosphere is pure hydrogen or a mixture of hydrogen and an inert gas, preferably a hydrogen / argon mixture, and the hydrogen concentration is 5-10% by volume. The reduction time is preferably 1-2 hours. Catalyst powder is obtained.

[0019] The adjustable-loading noble metal (0-2 wt%)-cerium single-atom (1-10 wt%) catalyst material is in solid powder form. In this catalyst material, the mass percentage of noble metal is 0-2%, and the mass percentage of cerium is 1-10%.

[0020] This invention discloses the application of the aforementioned catalyst or the catalyst prepared according to the aforementioned method in the catalytic reforming of methane with carbon dioxide.

[0021] This invention further protects a solid-phase catalytic reaction for methane and carbon dioxide reforming. In this gas-solid-phase catalytic reaction, methane and carbon dioxide are used as raw materials, and the aforementioned ruthenium or rhodium nanoparticle-cerium single-atom catalyst material is used as a catalyst to catalyze the reforming reaction to prepare syngas (carbon monoxide and hydrogen). The ratio of CH4 to CO2 in the raw material gas is 1:1, the N2 content is 0-60%, the reaction pressure is atmospheric pressure, the flow rate of the reaction gas is 50-150 mL / min, and the mass of the added catalyst is 10-30 mg.

[0022] Beneficial effects

[0023] The catalyst of the present invention has the following effects:

[0024] 1. This invention provides a noble metal-cerium catalyst material with adjustable loading and its preparation method. Using commercially available oxides γ-Al₂O₃, SiO₂, and TiO₂ as supports, the catalyst undergoes solvent removal, high-temperature calcination, and high-temperature reduction to generate noble metal nanoparticle-cerium single-atom catalyst material. This method has advantages such as simple operation, flexible and adjustable composition, scalable yield, low raw material cost, environmental friendliness, and good reproducibility.

[0025] 2. The rhodium nanoparticle-cerium single-atom catalyst of this invention exhibits excellent catalytic activity and stability in the methane-carbon dioxide reforming reaction, particularly its outstanding resistance to sintering and carbon deposition. In long-term stability tests, the catalyst can operate stably for over 1000 hours.

[0026] 3. The noble metal rhodium nanoparticle-cerium single-atom catalyst material of the present invention can replace the noble metal with other elements such as ruthenium and platinum. It has broad potential research and application value in other catalytic reactions. Attached Figure Description

[0027] Figure 1 The image shown is an aberration-corrected high-angle annular dark-field scanning electron microscope (AC-HAADF-STEM) image of the Rh nanoparticle-Ce single-atom catalyst material (1.0 wt% rhodium content and 10 wt% cerium content) supported by γ-Al2O3 in Example 1.

[0028] Figure 2 The X-ray powder diffraction (XRD) results are shown for the Rh nanoparticle-Ce single-atom catalyst material (1.0 wt% rhodium content and 10 wt% cerium content) supported on γ-Al2O3 in Example 1, after being reduced by hydrogen at 750°C for different times.

[0029] Figure 3 This is an aberration-corrected high-angle annular dark-field scanning electron microscope (AC-HAADF-STEM) image of the Ce single-atom catalyst material (cerium content 5 wt%) supported on γ-Al2O3 in Comparative Example 3.

[0030] Figure 4 High-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image (a) of the Ru nanoparticle-Ce single-atom catalyst material (ruthenium content 1.0 wt%, cerium content 10 wt%) supported on γ-Al2O3 in Example 6, and its catalytic performance on methane-carbon dioxide reforming (b).

[0031] Figure 5 High-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image (a) of the Pt nanoparticle-Ce single-atom catalyst material (1.0 wt% platinum content, 10 wt% cerium content) supported on γ-Al2O3 in Example 7, and its catalytic performance on methane-carbon dioxide reforming (b).

[0032] Figure 6 The image shows a high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image (a) of the Rh nanoparticle-Ce single-atom catalyst material (1.0 wt% rhodium content, 10 wt% cerium content) supported on TiO2 in Example 8, and its catalytic performance on methane-carbon dioxide reforming (b).

[0033] Figure 7 The image shows a high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image (a) of the Ce single-atom catalyst material (1.0 wt% rhodium content, 10 wt% cerium content) supported on Rh nanoparticles-SiO2 in Example 9, and its catalytic performance on methane carbon dioxide reforming (b).

[0034] Figure 8 The temperature-dependent catalytic activity diagrams for methane-carbon dioxide reforming of Rh nanoparticle-Ce single-atom catalyst material supported by γ-Al2O3 in Example 1 (rhodium content 1.0 wt%, cerium content 10 wt%), Rh nanoparticle catalyst material supported by γ-Al2O3 in Comparative Example 1, and Rh nanoparticle catalyst material supported by CeO2 in Comparative Example 2 (all with rhodium content 1.0 wt%).

[0035] Figure 9 The isothermal catalytic stability diagram of the Rh nanoparticle-Ce single-atom catalyst material (1.0 wt% rhodium content, 10 wt% cerium content) supported on γ-Al2O3 for methane carbon dioxide reforming is shown in Example 1.

[0036] Figure 10 This is a transmission electron microscope (TEM) image of the Rh nanoparticle catalyst material (1.0 wt%) supported on γ-Al2O3 as Comparative Example 1.

[0037] Figure 11 This is a high-resolution transmission electron microscope (HR-TEM) image of the Rh nanoparticle catalyst material (1.0 wt%) supported on CeO2, which is Comparative Example 2.

[0038] Figure 12The images show the Raman spectra of Rh nanoparticle-Ce single-atom catalyst material (cerium content 10 wt%) supported by γ-Al2O3 in Example 1, Rh nanoparticle catalyst material (rhodium content 1.0 wt%) supported by γ-Al2O3 in Comparative Example 1, and Rh nanoparticle catalyst material (rhodium content 1.0 wt%) supported by CeO2 in Comparative Example 2 after catalytic reforming of methane and carbon dioxide. Detailed Implementation

[0039] in

[0040] The Al2O3 support was a γ-phase, purchased from Alfa-Aesar; the SiO2 support was an aerosol, purchased from aladdin; the TiO2 support was Degussa P25, purchased from Sigma-Aldrich; and the CeO2 support was purchased from aladdin.

[0041] TEM: Transmission electron microscopy

[0042] HR-TEM: High-resolution transmission electron microscopy

[0043] HAADF-STEM: High-angle annular dark-field scanning electron microscope

[0044] AC-HAADF-STEM: Aberration-corrected high-angle annular dark-field scanning electron microscope

[0045] XRD: X-ray powder diffraction

[0046] The following will use specific embodiments to describe in detail the preparation method of the noble metal nanoparticle-Ce single-atom catalytic material provided by the present invention.

[0047] Example 1-5Rh-Ce / Al2O3

[0048] A. Carrier pre-reduction

[0049] The γ-Al2O3 support was placed in a 10% H2 / Ar atmosphere and heated to 350°C at a rate of 10°C / min, and then treated at 350°C for 2 hours.

[0050] B. Preparation and impregnation of precursor solutions

[0051] a. Dissolve 0.002-0.019g ammonium chlororhodium and 0.014-0.142g cerium nitrate in 20mL of deionized water and stir for 5min until completely dissolved to form a precursor solution.

[0052] b. Add 0.5g of reduced γ-Al2O3 support to the above precursor solution and stir for 0.5h to form a precursor mixture.

[0053] C. Desolventization and high-temperature calcination

[0054] a. The obtained precursor mixture is rotary evaporated at 60°C until the solvent is completely removed, forming a white powder.

[0055] b. Heat the white powder to 400°C at a rate of 10°C / min, and then treat it at 400°C for 4 hours to obtain a light pink powder.

[0056] D. High-temperature reduction of hydrogen

[0057] The obtained solid powder was placed in a 10% H2 / Ar atmosphere and heated to 750°C at a rate of 10°C / min, and then treated at 750°C for 1 hour.

[0058] Catalysts with varying Rh loadings were prepared using the same method: 1. Catalysts with Rh loadings of 0.1%, 0.5%, and 1.0% when the Ce loading was 10%; 2. Catalysts with Ce loadings of 1%, 5%, and 10% when the Rh loading was 1%. In the preparation of the series of Rh-Ce / Al₂O₃ samples with varying Rh loadings, 0.142 g of cerium nitrate was added, resulting in a Ce loading of 10 wt%; 0.002 g of ammonium rhodium chloroester was added, resulting in an Rh loading of 0.1 wt%; and 0.019 g of ammonium rhodium chloroester was added, resulting in an Rh loading of 1 wt%. In the preparation of a series of Rh-Ce / Al2O3 samples with varying Ce loading, the addition of 0.019 g of ammonium chlororhodium resulted in a Ce loading of 1 wt%; the addition of 0.071 g of cerium nitrate resulted in a Ce loading of 5 wt%; and the addition of 0.142 g of cerium nitrate resulted in a Ce loading of 10 wt%.

[0059] Catalysts for Examples EX1-EX5 were formed.

[0060] EX1 is Rh 1% Ce 10% / γ-Al2O3

[0061] EX2 is Rh 1% Ce 5% / γ-Al2O3

[0062] EX3 is Rh 1% Ce 1% / γ-Al2O3

[0063] EX4 is Rh 0.5% Ce 10% / γ-Al2O3

[0064] EX5 is Rh 0.1% Ce 10% / γ-Al2O3

[0065] Among them, the aberration-corrected high-angle annular dark-field scanning electron microscope (AC-HAADF-STEM) image of the catalyst of Example 1 (EX1) (Rh loading of 1% and Ce loading of 10%) is shown in [reference]. Figure 1 See its X-ray powder diffraction (XRD) image. Figure 2 The temperature-dependent catalytic activity for methane-carbon dioxide reforming is shown in [reference needed]. Figure 8 Long-term stability at constant temperature is shown in the figure. Figure 9 The Raman spectrum of the catalyst after the reaction is shown below. Figure 12 .

[0066] Example 6 Ru-Ce / Al2O3

[0067] The specific implementation conditions are the same as in Example 1, except that the precious metal is replaced with ruthenium. The Ce loading is 10%; the Ru loading is 1%.

[0068] The aberration-corrected high-angle annular dark-field scanning transmission electron microscope (AC-HAADF-STEM) images of the catalyst and its catalytic activity for methane-carbon dioxide reforming are shown in [reference needed]. Figure 4 .

[0069] Example 7 Pt-Ce / Al2O3

[0070] The specific implementation conditions are the same as in Example 1, except that the precious metal is replaced with platinum. The Ce loading is 10%; the Pt loading is 1%.

[0071] The aberration-corrected high-angle annular dark-field scanning transmission electron microscope (AC-HAADF-STEM) images of the catalyst and its catalytic activity for methane-carbon dioxide reforming are shown in [reference needed]. Figure 5 .

[0072] Example 8 Rh-Ce / TiO2

[0073] The specific implementation conditions are the same as in Example 1, except that the support is replaced with TiO2. The Ce loading is 10%; the Pt loading is 1%.

[0074] The high-angle annular dark-field scanning electron microscope (HAADF-STEM) image of the catalyst and its catalytic activity for methane-carbon dioxide reforming are shown in [reference needed]. Figure 6 .

[0075] Example 9 Rh-Ce / SiO2

[0076] The specific implementation conditions are the same as in Example 1, except that the support is replaced with SiO2. The Ce loading is 10%; the Pt loading is 1%.

[0077] The high-angle annular dark-field scanning electron microscope (HAADF-STEM) image of the catalyst and its catalytic activity for methane-carbon dioxide reforming are shown in [reference needed]. Figure 7.

[0078] Comparative Example 1: Rh / Al2O3

[0079] The specific implementation conditions are the same as in Example 1, except that cerium is not added. The Rh loading is 1%. The temperature-dependent catalytic activity for methane-carbon dioxide reforming is shown in [reference needed]. Figure 8 The transmission electron microscope (TEM) image of the catalyst after the reaction is shown below. Figure 10 The Raman spectrum of the catalyst after the reaction is shown below. Figure 12 .

[0080] Comparative Example 2Rh / CeO2

[0081] The specific implementation conditions are the same as in Example 1, except that the support is replaced with CeO2. The Rh loading is 1%. The temperature-dependent catalytic activity for methane-carbon dioxide reforming is shown in [reference needed]. Figure 8 High-resolution transmission electron microscopy (HR-TEM) images of the catalyst after the reaction are shown below. Figure 11 The Raman spectrum of the catalyst after the reaction is shown below. Figure 12 .

[0082] Comparative Example 3Ce / Al2O3

[0083] The specific implementation conditions are the same as in Example 1, except that no precious metals are added and the Ce loading is 10%.

[0084] See aberration-corrected high-angle annular dark-field scanning electron microscope (AC-HAADF-STEM) image of the catalyst with 10% Ce loading. Figure 3 .

[0085] Application testing experiments and data

[0086] The activity test of methane-carbon dioxide reforming was conducted in a fixed-bed reactor. First, 20 mg (20-40 mesh) of the catalyst to be tested was loaded into a quartz reaction tube, and a reaction gas mixture of CH4:CO2:N2 (1:1:3) was introduced. The temperature was increased to 600℃, 650℃, 700℃, and 750℃ at a rate of 10℃ / min, and held at each temperature for 1 h. The catalytic activity of the catalyst at the corresponding temperatures was then measured. The reaction space velocity was 400 L / g. –1 h –1 The real-time components of the gases were detected by an online gas chromatograph (Shimadzu 2014) (equipped with a TCD detector and a TDX-01 carbon molecular sieve column). The reaction conversion rate was calculated using the integrated peak areas of methane, carbon dioxide, and nitrogen. The relevant results are shown in the following formula:

[0087] X CH4 =((n) CH4 / n N2 ) in -(n CH4 / nN2 ) out ) / (n CH4 / n N2 ) in ×100%

[0088] X CO2 =((n) CO2 / n N2 ) in -(n CO2 / n N2 ) out ) / (n CO2 / n N2 ) in ×100%

[0089] n CH4 n CO2 n N2 These represent the peak areas of methane, carbon dioxide, and nitrogen, respectively; X CH4 and X CO2 These represent the conversion rates of methane and carbon dioxide, respectively.

[0090] Conclusions and Analysis

[0091] Analysis of the product structure showed that when Comparative Example 3 contained only Ce, Ce exhibited a densely dispersed single-atom structure on the surface of the γ-Al₂O₃ support (see [link]). Figure 3 ), combined Figure 1 It can be seen that the catalyst described in Example 1 exhibits a composite structure of Rh nanoparticles and Ce single atoms.

[0092] Depend on Figure 2 As can be seen, Example 1 without hydrogen reduction exhibits crystalline phases of γ-Al₂O₃ support and CeO₂ in X-ray diffraction. After hydrogen reduction at 750℃, the CeO₂ crystalline phase disappears. Extending the reduction time also results in only observing the crystalline phase of the γ-Al₂O₃ support, proving that both Rh nanoparticles and Ce single atoms are in a stable, highly dispersed state.

[0093] Depend on Figure 4-7 It is evident that Ru-Ce / Al2O3, Pt-Ce / Al2O3, Rh-Ce / SiO2, and Rh-Ce / TiO2 catalysts with similar metal particles—Ce single atoms—can be prepared using the same preparation method. During the catalytic reforming of methane with carbon dioxide, the carbon dioxide conversion rate is consistently slightly higher than the methane conversion rate due to the presence of the reverse water-gas shift side reaction. Therefore, the methane conversion rate is used as a reference for evaluating the activity and stability of the catalyst in the methane-carbon dioxide reforming process.

[0094] The catalytic performance test results of the catalysts used in the example application of methane carbon dioxide reforming are shown in Table 1.

[0095] Table 1 Application Test Data Table

[0096]

[0097] *EX indicates an example, and CEX indicates a comparative example. Methane conversion data are taken at the 9th hour.

[0098] Combined with Table 1 and Figure 8 It is evident that Examples 1-9 and Comparative Examples 1 and 2 all exhibit activity, with the Rh-Ce1 / Al2O3 and Rh-Ce1 / SiO2 systems showing the best catalytic performance. The optimal approach is Example 1, which demonstrates the best activity in the methane-carbon dioxide reforming reaction at 750°C. Furthermore, Example 1 can operate stably under these conditions for over 1000 hours. Figure 9 Comparative Example 1, after the reaction, shows the formation of carbon deposits. Figure 10 , 12 In contrast, in Comparative Example 2, the Rh particles underwent sintering and agglomeration after the reaction. Figure 11 In contrast, the catalyst in Example 1 not only exhibited high catalytic activity for methane and carbon dioxide, but its resistance to sintering and carbon deposition also made its catalytic stability more outstanding.

[0099] in conclusion:

[0100] The rhodium nanoparticle-cerium single-atom catalyst material prepared by this invention exhibits significantly better catalytic performance in the methane-carbon dioxide reforming to syngas reaction compared to rhodium-based catalyst materials without cerium single atoms, under the same rhodium content. The preparation method employed in this invention is simple, convenient, easy to operate, and easily scaled up. Even in harsh reaction atmospheres rich in H2 and CO at high temperatures, the catalyst material prepared by this invention can sustainably and stably catalyze the methane-carbon dioxide reforming reaction, demonstrating excellent resistance to carbon deposition and sintering.

[0101] Furthermore, those skilled in the art may make other changes within the spirit of this invention. Of course, all such changes made in accordance with the spirit of this invention should be included within the scope of protection claimed by this invention.

Claims

1. A noble metal nanoparticle-cerium single-atom catalyst, comprising a metal oxide support and noble metal nanoparticles and cerium single atoms supported thereon, wherein the oxide support is selected from any one, two, or a mixture of more than one of γ-Al₂O₃, SiO₂, and TiO₂; and the noble metal is rhodium and / or ruthenium; wherein, The noble metal is loaded on the support in the form of nanoparticles, and the cerium is loaded on the support in the form of single atomic sites; based on the total weight of the catalyst, the loading of the noble metal is 0.1-5% by mass; the loading of the cerium is 0.01-15% by mass.

2. The catalyst according to claim 1, wherein, Based on the total weight of the catalyst, the loading of precious metals is 0.1-2% by mass; the loading of cerium is 1-10% by mass.

3. The catalyst according to claim 1 or 2, wherein, The support is γ-Al2O3, SiO2, or TiO2.

4. The catalyst according to claim 3, wherein, The carrier is γ-Al2O3.

5. The catalyst according to claim 1 or 2, wherein the catalyst is Rh-Ce1 / Al2O3, Rh-Ce1 / SiO2, Rh-Ce1 / TiO2 or Ru-Ce1 / Al2O3.

6. A method for preparing the catalyst according to any one of claims 1-5, comprising the following steps: S1: Pre-reduction of the oxide support; S2: A solution is formed by mixing a soluble metal salt with a solvent, and then an oxide carrier is added and stirred until homogeneous; S3: The mixture obtained from S2 is desolventized and calcined at high temperature to obtain a solid powder; S4: Reduce the solid powder at high temperature to obtain catalyst powder; The oxide support is selected from any one, two or more of γ-Al2O3, SiO2, and TiO2; the soluble metal salt is composed of a soluble noble metal salt or a noble metal complex and a soluble cerium salt. The solvent is deionized water, or C 1-4 Alcohols.

7. The method according to claim 6, wherein, The soluble noble metal salt or noble metal complex is ruthenium nitrite, ammonium ruthenium chloride, rhodium nitrate, or rhodium chloride; the soluble cerium salt is selected from any one or a mixture of two of cerium nitrate, ammonium cerium nitrate, and cerium chloride.

8. The method according to claim 7, wherein, In step S1, the reduction is carried out in a reducing atmosphere at a temperature of 300-500 °C; the reducing atmosphere is pure hydrogen or a mixture of hydrogen and an inert gas, and the reduction time is 1-4 hours; the solvent is ethanol. The solvent removal method is selected from heating evaporation, vacuum evaporation, vacuum heating evaporation, or freeze drying. The high-temperature calcination temperature is 400-800 ℃, the calcination atmosphere is air, and the calcination time is 4-8 hours; In step S4, the reduction temperature is 600-800 ℃, the reduction atmosphere is pure hydrogen or a mixture of hydrogen and inert gas, and the reduction time is 1-2 hours.

9. The method according to claim 8, wherein, The hydrogen and inert gas are a hydrogen / argon mixture.

10. The application of the catalyst according to any one of claims 1-5, or the noble metal nanoparticle-cerium single-atom catalyst prepared according to any one of claims 6-9, in the catalytic reforming of methane with carbon dioxide.

11. A method for preparing syngas, wherein, Using methane and carbon dioxide as raw materials, and using the catalyst described in any one of claims 1-5 or the noble metal nanoparticle-cerium single-atom catalyst prepared by any one of claims 6-9, carbon monoxide and hydrogen are prepared by catalytic reforming reaction.

12. The method according to claim 11, wherein, The ratio of CH4 to CO2 in the feed gas is 1:1; the feed gas contains N2, with N2 accounting for 0-60%.

Citation Information

Patent Citations

  • Method for preparing catalyst for preparing synthesis gas by reforming methane and carbon dioxide

    CN101637726A